Fast Determination of Water Content of Some Organic Solvents by Smart Sensor Based on PPy-Ag Nanoco - Pirsa, Sajad (Nanoscience & Nanotechnology-Asia, 2016)
Background: In this work interaction of PPy-Ag fiber surface and some volatile organic compounds was investigated. PPy-Ag fiber sensor resistance is increased by interaction with all of organic compounds, but H2O decreases PPy-Ag fiber sensor resistance, so we can easily determine the water content of some organic compounds in nanogram levels (> 10 ng). As an innovation of this work, determination of water in organic compounds by PPy-Ag fiber sensor is done in several seconds (about 30 Sec). Furthermore, PPy-Ag sensor can determine volatile organic compounds and water concentration in a mixed solution at the same time. Methods: The PPy-Ag Nanocomposites were characterized by scanning electron microscopy (SEM) and FT-IR spectroscopy. The electrical resistance of polypyrrole-Ag fiber is strongly depended on the used doping and oxidant agents. The sensing behavior of PPy-Ag fibers in the presence of different organic solvents (in the gas phase) such as Water, Methanol, Ethanol, Acetone and so was studied experimentally. The mechanism of resistance change of sensor was investigated and the conditions that affect the determination of water were optimized. Results: Nanocomposites of polypyrrole-Ag were successfully synthesized via in situ chemical oxidation polymerization of pyrrole on the polyester fiber. Ferric chloride (FeCl3) as an oxidizing agent and silver nitrate (dopant) were used in nanocomposite polymerization. PPy-Ag gas sensor as a fast method was used to determine (30 seconds) water concentration in some organic solvents. According to the results the sensor had capability of simultaneous determination of water and solvent concentration in the gas phase. Conclusion: The resistance change of polypyrrole-Ag sensor and water concentration had a good linear relativity in the range of 4-60 ng. This technique has some advantages: low cost, good reproducibility, and sensitivity, operate simply, detect fast, safe to the environment and accurate determination of trace amounts of water in organic solvents.
Keywords: water content